As leis de Newton em atividades orientadoras de ensino: uma análise das elaborações conceituais de estudantes do ensino médio em um sistema prisional - Silva, Márcio Martins da (2015)
The objective of this research was to identify and analyze the conceptual elaborations produced by students of a prison system when Newton's laws are built on Guiding Teaching Activities (product). The research is grounded in a historical and cultural perspective of knowledge which aimed to understand the logical historical process of Newton's Laws to identify conceptual links that have been exploited in the design and product development. This process was guided by the following research question: What elaborations students of the first year of high school a prison system produce about the Newton's laws when this is developed from the exploration of its conceptual links in Guiding activities Teaching? It is a qualitative research whose documentation was constructed from the following data collection instruments: Sound Recorder, the written records produced by the students through the AOE, research professor of the field diary and shooting. Data analysis was guided on a methodology called content analysis, from which it was found that the registration units could be the very conceptual connections identified for Newton's laws: movement; force; and inertia. It was also found that students were placed in operation, discussed in groups, and that, in their interactions, there were arguments similar to those found in logical-historical process concept, which formed the basis for the teaching mediation and systematization of the concept.